Temperature stress on pristine ZnO nanowire field effect transistor - Kim, Kyoungwon; Debnath, Pulak Chandra; Kim, Sangsig; Lee, Sang Yeol (AMER INST PHYSICS, 2011)
We have investigated the effect of the temperature dependency on the device stability of pristine ZnO nanowires (NWs) field effect transistor (FET). Pristine ZnO NW FET shows a large threshold voltage (V(th)) shift by 6.5 V after increasing the measured temperature from 323 to 363 K. This large shift in V(th) is mainly due to thermally activated process. Thermally activated electrons from the deep level trap site can be free carriers which results in the shift in V(th) in negative direction. Also, activation energy of ZnO NW FET is derived to be about 1.432 eV based on thermally activated Arrhenius model. (C) 2011 American Institute of Physics. [doi:10.1063/1.3567795]
Keywords: FABRICATION